PFA-100 closure times in preoperative screening in 500 pediatric patients - Roschitz, Birgit; Thaller, Sigrid; Koestenberger, Martin; Wirnsberger, Andrea; Leschnik, Bettina; Fritsch, Peter; Muntean, Wolfgang (Thrombosis and Haemostasis, 2007)
Three to five percent of patients undergoing surgery have either an acquired or congenital platelet defect or von Willebrand disease (vWD). The predictive value of preoperative coagulation screening is questionable. PFA-100 is now routinely used in preoperative screening in our pediatric outpatient service. We wanted to assess whether the PFA-100 would help to identify patients with primary haemostatic defects or if the additional use of PFA-100 would add to the problem of unnecessary pathologic preoperative laboratory values resulting in delay of surgical procedure. We investigated 500 children consecutively seen in our outpatient service before surgery. Blood cell count, aPTT, PFA-100 closure times (CT) were done in all patients. If abnormalities were found, the patient was presented to a haemostatic expert. vWF:AG, R:Cof and factorVIII were analysed in all patients with prolonged closure times and APTT values. One hundred twenty-six patients (25.2%) showed abnormalities in APTT and/or PFA-100. Further investigations in 89 of these 126 patients did not yield a specific diagnosis; neither diagnostic criteria for impaired haemostasis were found by questionnaire. None of these 89 patients had a bleeding complication during surgery. Forty-eight patients showed prolonged CTs. Twelve patients with low vWF:AG were detected, 10 of these patients were found by PFA-100. Four of these patients did present with normal APTT values. Our study shows that similar to the APTT the PFA-100 is probably only a good screening method when a haemostatic defect in a patient is clinically likely, especially to screen forVWD, and the test should not be used in general unselective screening.
Keywords: Paediatric haemostasis; von Willebrand disease; closure time